Altered Coupling of Psychological Relaxation and Regional Volume of Brain Reward Areas in Multiple Sclerosis - Wakonig, Katharina; Eitel, Fabian; Ritter, Kerstin; Hetzer, Stefan; Schmitz-Hübsch, Tanja; Bellmann-Strobl, Judith; Haynes, John-Dylan; Brandt, Alexander U.; Gold, Stefan M.; Paul, Friedemann; Weygandt, Martin (Frontiers in Neurology, 2020)
Background: Psychological stress can influence the severity of multiple sclerosis (MS) but little is known about neurobiological factors potentially counteracting these effects. Objective: To identify grey matter (GM) brain regions related to relaxation after stress exposure in persons with MS (PwMS). Methods: 36 PwMS and 21 healthy controls (HCs) reported their feeling of relaxation during a mild stress task. These markers were related to regional GM volumes, heart rate, and depressive symptoms. Results: Relaxation was differentially linked to heart rate in both groups (t = 2.20, p = 0.017), i.e., both markers were only related in HCs. Relaxation was positively linked to depressive symptoms across all participants (t = 1.99, p = 0.045) although this link differed weakly between groups (t = 1.62, p = 0.108). Primarily the volume in medial temporal gyrus was negatively linked to relaxation in PwMS (t = -5.55, pFamily-Wise Error [FWE]-corrected = 0.018). A group-specific coupling of relaxation and GM volume was found in ventromedial prefrontal cortex (VMPFC) (t = -4.89, pFWE = 0.039). Conclusion: PwMS appear unable to integrate peripheral stress signals into their perception of relaxation. Together with the group-specific coupling of relaxation and VMPFC volume, a key area of the brain reward system for valuation of affectively relevant stimuli, this finding suggests a clinically relevant misinterpretation of stress-related affective stimuli in MS.